Open innovation in village-owned enterprises: the role of entrepreneurial orientation in improving financial and social performance - Fitri Wulandari; Marita Kusuma Wardani (Cogent Business & Management, 2024)
Unresolved issue regarding the role of entrepreneurial orientation in improving the financial and social performance of village-owned enterprises, as well as the importance of mediating the effect of open innovation, is the reason why this study was undertaken. The study involved 200 village-owned enterprises from 10 regencies in Central Java and Yogyakarta, Indonesia, and employed a purposive sampling method for data collection. Data analysis was conducted using SEM AMOS version 23. The results show that entrepreneurial orientation has an effect on financial performance and open innovation, but has no significant effect on social performance. Open innovation has a significant effect on social performance and financial performance. The research also supports the notion that open innovation acts as a mediator in the relationship between entrepreneurial orientation and financial and social performance. Therefore, the study recommends that village-owned enterprises should focus on increasing open innovation to improve performance, particularly in the social sphere, and that they should strive to retain managers with a high level of entrepreneurial orientation.The growth of BUMDes in tourism and trade has played an important role in creating jobs in the village, driving regional economic growth, and serving as a tool in reducing poverty in the village. BUMDEs as social enterprises in villages that have a vision to maximize profits while still providing social and environmental impacts. BUMDes is a social enterprise, having a vision of maximizing profits while providing social and environmental impacts. This study focuses on BUMDEs by looking at the potential and advantages of the village, because generally tourism and trading villages have potential in natural resources. Open innovation is expected to be a new energy for BUMDEs to make changes with new approaches and methods. It includes optimising internal resources and developing knowledge and experience from external sources. Open innovation encourages BUMDEs not only to rely on internal strengths, but also to increase opportunities for collaboration (partnership practices). Studies show that open innovation provides answers for BUMDEs to improve their social and financial performance. In addition, it is important for BUMDEs to be managed by managers with a strong entrepreneurial orientation who have persistence at work, proactive work behavior, competitive aggressiveness, courage to take measured risks, and innovativeness.
Keywords: 650; Entrepreneurial orientation; open innovation; financial performance; social performance; village-owned-enterprises/BUMDes